The Influence of Dietary Lipid Composition on Skeletal Muscle Mitochondria From Mice Following 1 Month of Calorie Restriction - Chen, Yana (Oxford University Press, 2012)
To investigate the role mitochondrial membrane lipids play in the actions of calorie restriction (CR), C57BL/6 mice were assigned to four groups (control and three 40% CR groups) and fed diets containing soybean oil (also in the control diet), fish oil, or lard. The fatty acid composition of the major mitochondrial phospholipid classes, proton leak, and H(2)O(2) production were measured in muscle mitochondria following 1 month of CR. The results indicate that phospholipid fatty acids reflected the polyunsaturated fatty acid profile of the dietary lipid sources. Capacity for Complex I– and III–linked H(2)O(2) production was decreased with CR, although there was no difference between CR groups. The CR lard group had lower proton leak than all other groups. The results indicate that a decreased degree of unsaturation in muscle mitochondrial membranes is not required for reduced H(2)O(2) production with CR. However, dietary lipids do have some influence on proton leak with CR.